MENINGKATKAN KEAKTIFAN SISWA MELALUI PENGGUNAAN VIDEO PERCAKAPAN: STUDI DI SMK AL-MALIKI LUMAJANG - Nur Laili Yusuf (PPPM STIT MIFTAHUL MIDAD, 2024)
This study aims to investigate enhancing student engagement through the use of video conversation at vocational school. This focuses on Indonesian students which most of them have some difficulties in speaking English, especially at SMK Al-Maliki Lumajang. This study used qualitative case study approach. The data was collected through some document analysis, classroom observation and interview. The result of this study were video conversations foster encouraged collaborative learning, enhanced visual learning, increased students interests, increased students interaction and participation, increased students' creativity. Besides that it was found that there were stronger sense of community among students, and immediate feedback and clarification from the teacher. Those are a powerful tool that effectively enhances student engagement, making learning more impactful and relevant.